Spin polarized surface resonance bands in single layer Bi on Ge(1 1 1). (13th April 2016) - Bottegoni, F; Calloni, A; Bussetti, G; Camera, A; Zucchetti, C; Finazzi, M; Duò, L; Ciccacci, F
Abstract: The spin features of surface resonance bands in single layer Bi on Ge(1 1 1) are studied by means of spin- and angle-resolved photoemission spectroscopy and inverse photoemission spectroscopy. We characterize the occupied and empty surface states of Ge(1 1 1) and show that the deposition of one monolayer of Bi on Ge(1 1 1) leads to the appearance of spin-polarized surface resonance bands. In particular, the C 3v symmetry, which Bi adatoms adopt on Ge(1 1 1), allows for the presence of Rashba-like occupied and unoccupied electronic states around the M ¯ point of the Bi surface Brillouin zone with a giant spin–orbit constant | α R |   = ( 1.4 ± 0.1 ) eV · Å.